Failure history-based routing protocol for mobile ad hoc networks - Batiha, Khalid; Khaled Ababneh, Aamal (International Journal of Engineering and Technology, 2020)
Mobile Ad-hoc NETworks (MANETs) are defined as a collection of mobile nodes that cooperate in order to operate. Nodes in MANETs should build and maintain routes in order to communicate. A routing algorithm is used to manage these routes. MANETs have dynamic topology because of node mobility. The probability of route failure increases when intermediate nodes have higher mobility. This study will propose a routing protocol that depends on the failure history of the nodes from which the route will constructed. The proposed protocol will be implemented over the existing Ad hoc On-Demand Distance Vector (AODV) routing protocol. It is expected that the proposed protocol will improve the packet delivery ratio in the network.Â